Carbon sequestration in semi-arid rangelands: Comparison of Pinus ponderosa plantations and grazing exclusion in NW Patagonia - Nosetto, Marcelo Daniel (2006)
The large global extension of arid and semi-arid regions together with their widespread degradation give these areas a high potential to sequester carbon. We explored the possibilities of semi-arid ecosystems to sequester carbon by means of rangeland exclusion and afforestation with Pinus ponderosa in NW Patagonia (Argentina). We sampled all pools where organic carbon accumulates in a network of five trios of adjacent grazed, non-grazed and afforested stands (age: 12–25 years, density 605–1052 trees ha 1 ). After 15 years since trees were planted, afforestation added 50% more C to the initial ecosystem carbon pool, with annual sequestration rate ranging 0.5–3.3 Mg C ha 1 year 1 . Carbon gains in afforested stands were higher above than below-ground (150% vs. 32%). Root biomass differences (374% more in afforested vs. grazed stands, p ¼ 0:0011) explained below-ground carbon contrasts whereas soil organic carbon showed no differences with afforestation. By contrast, grazing exclosures did not result in significant changes in the total carbon storage in comparison with the adjacent grazed stands (p ¼ 0:42) suggesting a slow ecosystem recovery in the time frame of this study (15 years of exclusion). Nevertheless, higher litter amount was found in the former (+53%, p ¼ 0:07). Neither, soil organic carbon nor root carbon showed significant differences between grazed and non-grazed conditions. Considering that more than 1.1 millions of hectares of the studied ecosystems are highly degraded and suitable for tree planting, afforesting this area could result in a carbon sequestration rate of 1.7 Tg C year 1 , almost 6% of the current fossil fuel emissions of Argentina; however environmental consequences which could emerge from this deep land use shift must be taken into account when afforestation program are being designed.